Pengaruh Kompensasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Giri Artha Sejahtera Jakarta Barat : The Effect of Compensation and Work Discipline on Employee Performance at PT Giri Artha Sejahtera, West Jakarta - Aldian Dwi Prasetio; Darkiman Ruminta; Dudi Duta Akbar (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
PT Giri Artha Sejahtera is a national company engaged in driving schools and has implemented competency-based training and certification for its management. This study aims to determine the effect of compensation and work discipline both partially and simultaneously on employee performance. The type of research data used is quantitative research using multiple linear regression model data analysis methods and data processed using SPSS. The sampling technique used is saturated sampling. The data sources used are primary data such as observation and distributing questionnaires. While secondary data is literature study through book and journal sources. The results of this study prove that compensation does not have a positive and significant effect partially on employee performance. The work discipline variable has a positive and significant effect partially on employee performance, and the compensation and work discipline variables have a positive and significant effect simultaneously on employee performance. Based on the results of the R-Square determination coefficient test (R2) compensation and work discipline have an effect of 62%.